Answer:
check 2nd and last box. :))
Explanation:
Ok, so I would work out the Area, then rule out a few of these options.
First of all, if you look closely, you can see that instead of an l(x), it's an l(w), which means that what l(w) equals, is a product of whatever l(x) is with w serving as its x (if that makes sense lol). so, we need to divide by w to figure out what l(x) is.
3x³+2x²-4x+5 (3x³+5)+(2x²-4) (3x³+5)+2(x+2)(x-2)<difference of two squares
x+2 ⇒ x+2 ⇒ x+2 so then the (x+2)'s cancel
and you're left with 3x³+5+2x-4 ⇒ 3x³+2x+1 which is l(x). Now you're ready to see what A(x) equals.
x(3x³+2x+1)+2(3x³+2x+1) =
[(3x^4)+2x²+x]+(6x³+4x+2) =
(3x^4)+6x³+2x²+5x+2=A(x)
So now you can rule out the answers. Number one can be done mentally, and it's not correct. Number 2 is definitely true. Number three we need to work out.
(3x^4)+6x³+2x²+5x+2 [(3x^4)+6x³] (the rest doesn't matter)⇒ 3x³(x+2)
x+2 ⇒ x+2
So then you're left with 3x³+2x²+5x+2 which is not equal to l(x), so the third option is false and ruled out. The fourth one you can just look at A(x) and conclude it's false, and the third one is very obviously true.